The Influence of WhatsApp Reminders and Spaced Repetition in the WilEnglish App on Vocabulary Retention - Fries Sigilipu; Fries Pileman Soa'e (Journal of Innovative and Creativity, 2025)
This study examines the effect of WhatsApp reminders and the spaced repetition technique in the WilEnglish app on vocabulary retention among English Education students at Universitas Kristen Tentena. Adopting a quantitative approach with a pretest-posttest control group experimental design, the study involved 50 students who were divided into experimental and control groups. The experimental group used the WilEnglish app with spaced repetition and WhatsApp reminders, while the control group received no reminders. The data were analyzed using an independent t-test and gain score. The results showed a significant improvement in the experimental group (p < 0.05) with a higher gain score. WhatsApp reminders increased engagement and learning consistency, supporting the effectiveness of mobile-based learning.